Unsustainable Fashion: SHEIN and the Fast Fashion Consumption Model - Degli Esposti, Piergiorgio; Mortara, Ariela; Roberti, Geraldina (Italian Sociological Review, 2024)
Fashion, which has always played an important role in the economy and culture of many countries, is a sector with a high environmental impact, responsible for significant water consumption and the production of a large amount of waste. In particular, fast fashion, a business model based on offering consumers new, cheap and trendy products, seems to be one of the main drivers of the constant quest for innovation in fashion products, with a consequent increase in the environmental and social impacts of this policy. Among the companies in the sector, the SHEIN platform, founded in China in 2008 under the name Zzko, has become a real competitor to global industry giants such as Inditex and H&M, leading to a business model that can be defined as ultra-fast fashion. The article presents the results of a qualitative research project aimed at understanding the consumption model, purchasing motivations and possible concerns about sustainability of young female Italian consumers who use the platform. To this end, 30 semi-structured interviews were conducted with a sample of university students, who are SHEIN customers, to identify their main purchasing motivations, their consumption habits, and the importance they attribute to sustainability issues. The results show that the main drivers for the platform success are the low price of the clothes and the wide variety of styles available. Students also proved to be quite sensitive to the issue of the company’s unsustainable production practices, although this awareness does not automatically translate into a decision to stop buying the brand’s products.